2015
DOI: 10.1007/s10549-015-3504-2
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo studies of the combination of IGF1R inhibitor figitumumab (CP-751,871) with HER2 inhibitors trastuzumab and neratinib

Abstract: The insulin-like growth factor I receptor (IGF1R) has been linked to resistance to HER2-directed therapy with trastuzumab (Herceptin). We examined the anti-tumor activity of figitumumab (CP-751,871), a human monoclonal antibody that blocks IGF1R ligand binding, alone and in combination with the therapeutic anti-HER2 antibody trastuzumab and the pan-HER family tyrosine kinase inhibitor neratinib, using in vitro and in vivo breast cancer model systems. In vitro assays of proliferation, apoptosis, and signaling, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…In another recent study, Chakraborty et al . 72 have reported that treatment of MCF-7 cells with a combination of an IGF-1R mAb and the HER2 targeting agents neratinib and trastuzumab resulted in synergistic growth inhibition of these breast cancer cells, supporting the need for further investigations on the therapeutic potential of co-targeting IGF-1R and HER family members in breast cancer.…”
Section: Discussionmentioning
confidence: 96%
“…In another recent study, Chakraborty et al . 72 have reported that treatment of MCF-7 cells with a combination of an IGF-1R mAb and the HER2 targeting agents neratinib and trastuzumab resulted in synergistic growth inhibition of these breast cancer cells, supporting the need for further investigations on the therapeutic potential of co-targeting IGF-1R and HER family members in breast cancer.…”
Section: Discussionmentioning
confidence: 96%
“… 47 It was associated with trastuzumab resistance in a subset of 155 patients with HER2+ metastatic BCs. 24 Studies in vitro have shown synergistic effects of met-formin 48 and also of figitumumab, 49 a human mAb that blocks IGF1R ligand binding, with anti-HER2 drugs.…”
Section: Mechanisms Of Resistance To Trastuzumabmentioning
confidence: 99%
“…A combination of figitumumab plus the HER2-targeted therapies, trastuzumab and neratinib (HER2 TKI), was shown to elicit a synergistic effect on enhancing cell apoptosis and reducing cell proliferation in the BT474 and MCF7 breast cancer cells lines (Table 2) (Chakraborty et al 2015). Indirectly targeting IGF1R overexpression in HER2-amplified breast cancers by the introduction of miR-630 into the cell can restore the sensitivity of the cell to different HER2 inhibitors and may have clinical benefit to prevent IGF1R-driven HER2-therapy resistance (Corcoran et al 2014).…”
Section: Her2 Amplified Breast Cancermentioning
confidence: 99%